Investigation of the Langdon effect on the nonlinear evolution of SRS from the early-stage inflation to the late-stage development of secondary instabilities. (1st December 2022) - Qiu, Jie; Hao, Liang; Cao, Lihua; Zou, Shiyang
Abstract: In a laser-irradiated plasma, the Langdon effect can result in a super-Gaussian electron energy distribution function (EEDF), imposing significant influences on stimulated backward Raman scattering (SRS). In this work, the influence of a super-Gaussian EEDF on the nonlinear evolution of SRS is investigated by the three wave coupling model simulation and Vlasov–Maxwell simulation for plasma parameters covering a wide range of kλ De from 0.19 to 0.48 at both high and low intensity laser drives. In the early stage of SRS evolution, it is found that besides the kinetic effects due to electron trapping (2018 Phys. Plasmas 25 100702), the Langdon effect can also significantly widen the parameter range for the absolute growth of SRS, and the time for the absolute SRS to reach saturation is greatly shortened by the Langdon effect within certain parameter regions. In the late stage of SRS, when secondary instabilities such as decay of the electron plasma wave to beam acoustic modes, rescattering, and Langmuir decay instability become important, the Langdon effect can influence the reflectivity of SRS by affecting secondary instabilities. The comprehension of the Langdon effect on nonlinear evolution and saturation of SRS would contribute to a better understanding and prediction of SRS in inertial confinement fusion.